(untitled) (Boletín de la Sociedad Zoológica del Uruguay, 2021)
The inventory of insects collected by the Section of Limnology in various aquatic environments of Uruguay between 1984 and 2007 is described with the aim of publicizing their entry into the Entomology Collection of the Faculty of Sciences. The samples include 10 orders, 43 families, and 41 genera.